Does subsidized care for toddlers increase maternal labor supply? Evidence from a large-scale expansion of early childcare - Kai-Uwe Müller; Katharina Wrohlich; Denise Sengül (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper assesses whether there is a causal link between the provision of publicly subsidized childcare and the labor supply of mothers. We contribute to the related quasi-experimental literature by focusing on mothers with children aged 1 to 3. The effects of full-time and part-time care are disentangled. We exploit spatial and temporal variation in the expansion of publicly subsidized childcare triggered by comprehensive policy reforms. The utilization of various data sets and a systematic comparison of estimation frameworks sheds light on this relationship under different identifying assumptions. The crucial point is whether identification is restricted to quasi-experimental variation within regions. We confirm previous findings by showing the sensitivity of results to the choice of the research design, in particular the source of variation. Relying on credible exogenous variation we do not find a significant impact of childcare expansion on mothers' extensive labor supply margin. We find, however, a significant effect at the intensive margin. Our results cast doubt on previous empirical findings in terms of identification and effect size.
Keywords: J22; J13; H43; 330